1977
DOI: 10.1128/iai.16.1.268-270.1977
|View full text |Cite
|
Sign up to set email alerts
|

Human rotavirus in lambs: infection and passive protection

Abstract: A human stool filtrate containing rotavirus which was administered orally to gnotobiotic lambs caused diarrhea, virus excretion, development of antibodies to rotavirus, and pathological changes in the villi of the small intestine. Thus, lambs may serve as experimental animals for the study of human rotavirus infections. This model system was used to study passive protection. Human immunoglobulin G (IgG) containing antibody to rotavirus was fed to lambs 24 to 78 h after birth, and the lambs were infected with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…TAKAHASm et al (48) in 1979 reported that 10 of 18 dogs (55.6 percent) in Aomori prefecture of Japan had antibody against calf rotavirus as determined by complement fixation test (CFT). Since both IFT and CFT detect only group-specific antibodies, and rotaviruses from one species can infect another species (5,8,34,36,46,50,51,52,55), it was not clear from these studies whether the antibodies in the dogs resulted from infection with distinctly canine rotavirus or with human or some other rotavirus.…”
Section: Discussionmentioning
confidence: 99%
“…TAKAHASm et al (48) in 1979 reported that 10 of 18 dogs (55.6 percent) in Aomori prefecture of Japan had antibody against calf rotavirus as determined by complement fixation test (CFT). Since both IFT and CFT detect only group-specific antibodies, and rotaviruses from one species can infect another species (5,8,34,36,46,50,51,52,55), it was not clear from these studies whether the antibodies in the dogs resulted from infection with distinctly canine rotavirus or with human or some other rotavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Protection by passively acquired rotavirus-specific antibodies in milk was induced against both homotypic and heterotypic virus challenge after parenteral immunization but only against homotypic challenge after oral "hyperimmunization." The capacity of parenteral immunization to induce protection against heterotypic virus challenge has been demonstrated by a number of investigators (Lecce et al, 1991;Losonsky et al, 1986a;Schaller et al, 1992;Snodgrass et al, 1977). In addition, parenteral immunization with various combinations of baculovirus-expressed whole vp4, vp6, and vp7, or vp4-or vp7-specific peptides linked to vp6, can induce antibodies that passively protect against homotypic or heterotypic rotavirus challenge (Ijaz et al, 1991;Mackow et al, 1990;Redmond et al, 1993).…”
Section: E Protection Against Disease By Passive Immunizationmentioning
confidence: 99%
“…Antibodies are transmitted across the placenta and can be detected in infants in the first weeks of life by FA and NT. Subclinical rotavirus infections have been reported from hospital nurseries (11, 28, 72) ; it may be that circulating antibodies are, at this age, protective, but the weight of evidence from observation of rotavirus infection in animals is against this (118,143,119).…”
Section: Immurdty In Manmentioning
confidence: 99%
“…Although rotavirus infection can cause clinical illness at all ages, it is most severe in calves of Jess than seven weeks of age, and commonly occurs within the first 7 days of life. Passive protection afforded by colostrum has limited value and vaccination of the dam has not resulted in much improvement, although early results suggested this might be advantageous (79,143,118,119):…”
Section: Immunity In Animal8mentioning
confidence: 99%